Reusability and Stability Tests of Calcium Oxide Based Catalyst (K2O/CaO-ZnO) for Transesterification of Soybean Oil to Biodiesel - Istadi Istadi; Udin Mabruro; Bintang Ayu Kalimantini; Luqman Buchori; Didi Dwi Anggoro (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2016)
This paper was purposed for testing reusability and stability of calcium oxide-based catalyst (K2O/CaO-ZnO) over transesterification reaction of soybean oil with methanol to produce biodiesel. The K2O/CaO-ZnO catalyst was synthesized by co-precipitation method of calcium and zinc nitrates followed by impregnation of potassium nitrate. The fresh and used catalysts were tested after regeneration. The catalysts were characterized by Scanning Electron Microscopy (SEM), X-ray Diffraction (XRD), and BET Surface Area in order to compare the catalyst structure between the fresh and used catalysts. The catalyst testing in transesterification proses was carried out at following operating conditions, i.e. catalyst weight of 6 wt.%, oil to methanol mole ratio of 1:15, and temperature of 60 oC. In addition, metal oxide leaching of K2O/CaO-ZnO catalyst during reaction was also tested. From the results, the catalysts exhibited high catalytic activity (80% fatty acid methyl ester (FAME) yield after three-cycles of usage) and acceptable reusability after regeneration. The catalyst also showed acceptable stability of catalytic activity, even after three-cycles of usage.